2010
DOI: 10.1111/j.1398-9995.2010.02383.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific recommendations for PROs and HRQoL assessment in allergic rhinitis and/or asthma: a GA2LEN taskforce position paper

Abstract: The GA(2)LEN taskforce on Patient-Reported Outcomes (PROs) and Health-Related Quality of Life (HRQoL) published in 2009 a position paper concerning PROS and HRQoL assessment in clinical trials on allergy. Because of the specificity of this topic in asthma and rhinitis, specific recommendations are needed. The aim of this position paper is to define PROs and their meaning in asthma and rhinitis research, explore the available tools to provide criteria for a proper choice, identify patient-related factor which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 100 publications
0
49
0
Order By: Relevance
“…Some of these measures have already been validated. Moreover, certain tools for patient-reported outcomes and their practical use in clinical trials have been reported in the GA 2 LEN recommendations (93). Under these recommendations, the Pediatric Allergic Disease Quality of Life Questionnaire (PADQLQ; 94) as well as the RQLQ, as disease-specific questionnaires, assess the disease from the patients' perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these measures have already been validated. Moreover, certain tools for patient-reported outcomes and their practical use in clinical trials have been reported in the GA 2 LEN recommendations (93). Under these recommendations, the Pediatric Allergic Disease Quality of Life Questionnaire (PADQLQ; 94) as well as the RQLQ, as disease-specific questionnaires, assess the disease from the patients' perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…HRQoL is a broad-ranging concept incorporating, in a complex way, the person’s physical and mental health, level of independence, social relationships, well-being and satisfaction [10,11]. Due to its multidimensional nature, HRQoL can be approached from different angles.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Essentially, researchers interested in developing versions for their country/language are invited to participate in the process, which is described in detail at http://caratnetwork.org, a dedicated website which also contains a web tool to help researchers follow the stipulated protocol.…”
Section: Cross-cultural Adaptationsmentioning
confidence: 99%